2013
DOI: 10.1021/la3044889
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Dark and Light-Enhanced Bactericidal Action of Cationic Conjugated Polyelectrolytes and Oligomers

Abstract: A multiscale investigation was carried out to study the dark and light-enhanced bactericidal mechanisms of poly(phenylene ethynylene) (PPE)-based cationic conjugated polyelectrolytes (CPEs) and oligo-phenylene ethynylenes (OPEs). On the morphological scale, Gram-negative E. coli cells exposed to CPE and OPE compounds in the dark show damage to the cell envelope, plasma membrane, and in some cases the cytoplasm, while with UV-irradiation, E. coli sustained catastrophic damages to both the cell envelope and cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(172 citation statements)
references
References 43 publications
7
165
0
Order By: Relevance
“…26 In addition, ROS destroy the ligation moieties of nucleic acids, base and sugar groups, and subsequently suspend DNA replication. 27 Furthermore, generation of ROS leads to the modification of amino acid side chains of proteins, causing degradation. Damaged proteins subsequently affect 25 (capt) 18 cluster-mediated photodynamic effects intracellular pathways and disturb cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In addition, ROS destroy the ligation moieties of nucleic acids, base and sugar groups, and subsequently suspend DNA replication. 27 Furthermore, generation of ROS leads to the modification of amino acid side chains of proteins, causing degradation. Damaged proteins subsequently affect 25 (capt) 18 cluster-mediated photodynamic effects intracellular pathways and disturb cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Damaged proteins subsequently affect 25 (capt) 18 cluster-mediated photodynamic effects intracellular pathways and disturb cellular metabolism. 27 Ichinose-tsuno et al 28 reported that aPDT using toluidine blue O and red LED facilitated an inhibitory effect on plaque formation. Fontana et al 29 and O'Neill et al 30 showed that application of dye photosensitizers, including MB and toluidine blue O, under red light irradiation inhibited plaque formation and significantly increased bacterial cell death and destruction of biofilms in the oral cavity, suggesting that 1 O 2 could penetrate dental plaque and subsequently cause destruction through antimicrobial effects.…”
Section: Discussionmentioning
confidence: 99%
“…10−12 The cytoplasm of Gram-negative bacteria has been shown to be destroyed by the corrosive radicals. 10 Because of the general mechanism(s) by which CPEs and OPEs inactivate bacteria and viruses, we investigate in this study the utility of the compounds as antifungal agents. The antifungal activities of a set of antimicrobial CPEs and OPEs against the vegetative eukaryotic Saccharomyces cerevisiae (S. cerevisiae) cells and ascospores/asci were measured.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, the antibiotic efficiency of the polymers was significantly enhanced. Similar antibiotic activity was also observed by Wang et al 190 when comparing the antibiotic action of a library of PPE polyelectrolyte and oligomer derivatives.…”
Section: Mixing Different Biocidal Polymerssupporting
confidence: 84%